Endocannabinoid basis of personality—Insights from animal model of social behavior - Kogan, Natalya M.; Begmatova, Dilorom; Vinnikova, Liudmila; Malitsky, Sergey; Itkin, Maxim; Sharon, Eyal; Klinov, Artem; Gorelick, Jonathan; Koman, Igor; Vogel, Zvi; Mechoulam, Raphael; Pinhasov, Albert (Frontiers in Pharmacology, 2023)
The endocannabinoid system is known to be involved in learning, memory, emotional processing and regulation of personality patterns. Here we assessed the endocannabinoid profile in the brains of mice with strong characteristics of social dominance and submissiveness.A lipidomics approach was employed to assess the endocannabinoidome in the brains of Dominant (Dom) and Submissive (Sub) mice. The endocannabinoid showing the greatest difference in concentration in the brain between the groups, docosatetraenoyl ethanolamine (DEA), was synthesized, and its effects on the physiological and behavioral responses of Dom and Sub mice were evaluated. mRNA expression of the endocannabinoid receptors and enzymes involved in PUFA biosynthesis was assessed using qRT-PCR.Results: Targeted LC/MS analysis revealed that long-chain polyunsaturated ethanolamides including arachidonoyl ethanolamide (AEA), DEA, docosatrienoyl ethanolamide (DTEA), eicosatrienoyl ethanolamide (ETEA), eicosapentaenoyl ethanolamide (EPEA) and docosahexaenoyl ethanolamide (DHEA) were higher in the Sub compared with the Dom mice. Untargeted LC/MS analysis showed that the parent fatty acids, docosatetraenoic and eicosapentaenoic, were higher in Sub vs. Dom. Gene expression analysis revealed increased mRNA expression of genes encoding the desaturase FADS2 and the elongase ELOVL5 in Sub mice compared with Dom mice. Acute DEA administration at the dose of 15 mg/kg produced antinociceptive and locomotion-inducing effects in Sub mice, but not in Dom mice. Subchronic treatment with DEA at the dose of 5 mg/kg augmented dominant behavior in wild-type ICR and Dom mice but not in Sub mice.This study suggests that the endocannabinoid system may play a role in the regulation of dominance and submissiveness, functional elements of social behavior and personality. While currently we have only scratched the surface, understanding the role of the endocannabinoid system in personality may help in revealing the mechanisms underlying the etiopathology of psychiatric disorders.